FEops in structural heart interventions : how to prepare data for AI-enabled anatomical analysis - Reis, Mara Vieira (My University, 2024)
Structural heart diseases are a group of abnormalities in the heart that interfere with heart muscle, walls, chambers, or valves. They are present at birth (congenital), or they can appear over time. These conditions can be manifested as chest pain, shortness of breath, fatigue, or even heart failure. This report mentions two types of interventional procedures for the treatment of structural heart diseases: Transcatheter Aortic Valve Implantation (TAVI) and Left Atrial Appendage Occlusion (LAAO). These minimally invasive procedures have a positive impact on structural heart diseases as they reduce symptoms such as chest pain, breathlessness, stroke and improve quality of life. The internship described in this report was performed at the company FEops in Belgium, being part of the team as a Case Analyst and lasted six months. During the internship, the intern had access to real patient cases, using the Materialise Mimics software transferring Computed Tomography data to anatomical 3D models, taking landmarks and measurements of the patient's heart. The data is patient-specific and linked to different therapies (Transcatheter Aortic Valve Implantation and Left Atrial Appendage Occlusion) of structural heart diseases. The aim of the process at FEops is to create medical devices that are compatible with each patient, considering the purpose of the device, whether it 's for Implanting an Aortic Valve or Occluding the Left Atrial Appendage. The intern was involved in the first stage of this process, with the next step being to analyze more anatomical structures and take any measurement necessary for the intended result. In this report, the intern describes general information about the anatomy and functioning of the heart, describes in detail the use of Mimics software, as well as the 3D Slicer software. During this internship the intern was involve in more than two hundred cases. This report shows that working with Mimics software can be used to improve pre- procedure planning, enhance patient-specific care, and improve procedural outcomes in Transcatheter Aortic Valve Implantation and Left Atrial Appendage Occlusion procedures. Additionally, the 3D Slicer software is explained, which is used to automatically detect the coronary artery appearance and, consequently, determine the percentage of stenosis evolution, by analyzing the patient 's image before the intervention of the medical device.

As doenças cardíacas estruturais são um grupo de anomalias do coração que interferem com o músculo cardíaco, as paredes, as câmaras ou as válvulas. Normalmente, estão presentes à nascença (congénitas) ou podem aparecer ao longo do tempo. Estas condições podem manifestar-se sob a forma de dor no peito, falta de ar, fadiga ou mesmo insuficiência cardíaca. Neste relatório são mencionados dois tipos de procedimentos de intervenção para o tratamento das doenças estruturais do coração existem dois: Implante Transcateter de Válvula Aórtica e Oclusão do Apêndice Atrial Esquerdo. Estes procedimentos minimamente invasivos têm um impacto positivo nas doenças estruturais do coração, uma vez que reduzem o risco os sintomas como dor no peito, a falta de ar, o enfarte e melhoram a qualidade de vida. O estágio descrito neste relatório foi realizado na empresa FEops, na Bélgica, integrando a equipa como Analista de Casos. Durante o estágio, o estagiário utilizou o software Mimics, transferindo dados de tomografia computorizada para modelos anatómicos 3D, obtendo pontos de referência e medições do coração do paciente. Os dados são específicos do doente e estão associados a diferentes terapias (Implante Transcateter de Válvula Aórtica e Oclusão do Apêndice Atrial Esquerdo) de doenças cardíacas estruturais. Neste relatório, o estagiário descreve informações gerais sobre a anatomia e o funcionamento do coração, descreve em pormenor a utilização do software Mimics e descreve o software 3D Slicer. Este relatório mostra que o trabalho com o software Mimics pode ser utilizado para melhorar o planeamento pré-procedimento, melhorar os cuidados específicos do doente e melhorar os resultados do procedimento nos procedimentos de Implante Transcateter de Válvula Aórtica e de Oclusão do Apêndice Atrial Esquerdo. Além disso, é explicado o software 3D Slicer, que é utilizado para detetar automaticamente o aspeto da artéria coronária e, consequentemente, determinar a percentagem de evolução da estenose.
Keywords: Doenças cardíacas estruturais; Implante Transcateter de Válvula Aórtica; Oclusão do Apêndice Atrial Esquerdo; Software Mimics